Fluorescence in situ hybridization with rDNA probes on chromosomes of two nucleolus organizer region phenotypes of a species of Eigenmannia (Pisces, Gymnotoidei, Sternopygidae) - De Almeida-Toledo, Lurdes Foresti; Stocker, Ann Jacob; Foresti, Fausto [UNESP]; De Almeida Toledo-Filho, Silvio (Springer Nature, 1996)
Nucleolus organizer regions (NORs) were analysed in two related and geographically close populations of Eigenmannia sp.1 (Pisces, Gymnotoidei, Sternopygidae) using silver staining and fluorescence in situ hybridization (FISH). The two populations differed in their AS-NOR phenotypes, displaying fixed differences in the NOR-bearing chromosome pairs. FISH with rDNA probes showed that these differences were due to the location of rDNA cistrons. This finding, showing fixed NOR differences between two populations belonging to the same species in a connected river system, is highly significant in terms of evolutionary change, possibly indicating an initial step of genetic differentiation. This result also has important implications from the cytosystematic point of view, as NORs usually have a very constant karyotypic location in fish species and have been used as species-specific chromosome markers.
Keywords: Cytogenetics; Fluorescence in situ hybridization; Gymnotoidei; Nucleolus organizer region; Pisces; ribosome dna; animal tissue; chromosome analysis; chromosome NOR; cistron; dna probe; evolution; fish; fluorescence in situ hybridization; nonhuman; population genetics; priority journal; silver staining; Animals; Brazil; Chromosome Banding; DNA Probes; DNA, Ribosomal; Electric Fish; Female; In Situ Hybridization, Fluorescence; Karyotyping; Male; Nucleolus Organizer Region; Phenotype; Animalia; Eigenmannia; Eigenmannia sp.; Sternopygidae